2016
DOI: 10.1557/jmr.2016.372
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and magnetic properties of spark plasma sintered soft magnetic FeCo alloy reinforced by carbon nanotubes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…Therefore, improving the ductility and toughness of increase in ductility. The ductility of the samples sintered at 1100 ºC without dwelling is higher than the recently reported ductility of FeCo alloy composites prepared by spark plasma sintering under 80 MPa pressure, at 900 ºC for 3 min [29,33].…”
Section: Mechanical Propertiescontrasting
confidence: 67%
See 2 more Smart Citations
“…Therefore, improving the ductility and toughness of increase in ductility. The ductility of the samples sintered at 1100 ºC without dwelling is higher than the recently reported ductility of FeCo alloy composites prepared by spark plasma sintering under 80 MPa pressure, at 900 ºC for 3 min [29,33].…”
Section: Mechanical Propertiescontrasting
confidence: 67%
“…Samples sintered under 80 MPa in previous work [29], achieved near-full densification to a relative density of 99.1 %. However, it has been shown here that it is possible to obtain a relative density of 99.4 % at a significantly lower compaction pressure of 50 MPa.…”
Section: Effect Sps Parameters On Densification and Structurementioning
confidence: 77%
See 1 more Smart Citation
“…% CNT composite as compare to monolithic FeCo alloy with further extending in ball-milling time. It was found that the uniform dispersed CNTs in FeCo alloy to cause an increase in saturation induction with reduced coercivity, due to improve densification and formation nanocrystallite ordered structure [28].…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…2 SPS recently used for sintering FeCo alloy composites, showing an advantage for maintaining the nanostructure features and significant improvement in mechanical properties. [3][4][5] Newly, the mechanical properties of FeCo alloy were significantly improved by SPS at certain sintering conditions. 6 Therefore, the current study aims to evaluate the magnetic properties of FeCo alloy sintered at different sintering conditions in order to optimise the best sintering conditions for the best combination of magnetic and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%